The Effectiveness of Problem Based Learning Model on the Ability to Solve Mathematical Problems in terms of Students' Analytical Thinking Ability - Umar Ahmad Purba; Zainal Azis (JMEA : Journal of Mathematics Education and Application, 2022)
The problem that underlies this research is the low ability of students to solve problems related to math problems which results in decreased activity, innovation and creativity in learning. Based on these problems, this study aims to determine whether the PBL. Model effective in improving the ability to solve mathematical problems. This research is a quasi-experimental research with a quantitative approach. The population in this study was all grade VII students of SMPN 2 Kualasimpang in the academic year 2020/2021 while the research sample was grade VII-A students. Data analysis was carried out by using paired t-test and normalized gain . Based on the results of data analysis, the value of sig (2-tailed) is 0.000 0.05, which means that there is a difference in the average problem-solving ability before and after learning with the PBL model. The results of the calculation of the N-gain test above, show that the average value of the N-gain score for the ability to solve problems using the problem based learning model is 60.68%, which is included in the quite effective category. Thus H0 is rejected. This means that the problem-based learning model is effective in improving the ability to solve mathematical problems.